Correlation of Picky Eating in Children’s Growth: A Systematic Review - Dona Muji Fitriana; Risna Nur Pradany; Apriana Rahmawati (Jurnal Ners, 2019)
Introduction: picky eating is a problem that is now common in children, characterized by not trying or limiting variations in food, especially vegetables and fruit. Picky eating has an important role in the development of children, both physically and emotionally, so that it becomes a concern for the parents.Method: this systematic review aims to explain the correlation of picky eating on a child's growth using PRISMA approach from two database: Scopus and Proquest limited to the last 5 years; from 2015-2019 and obtained 15 articles that selected. Identification of articles using keywords ('picky eating' AND 'children' AND 'weight' or 'growth').Result: according to the findings, it was found nine articles that mentioned picky eating had an effect on growth and six articles mentioned no effect. Limitation of this study is that there are other factors that influence picky eating in selected articles.Conclusion: the most of the result from the studies show the behavior of picky eating in children can affect the growth of both body weight and height, and can also affect nutritional status, emotional status, physical activity and health status. Nurses can provide education about the effects of picky eating behavior on children in parents.